Vegetable Oil-Based Resins Reinforced with Spruce Bark Powder and with Its Hydrochar Lignocellulosic Biomass - Dinu, Roxana; Bejenari, Iuliana; Volf, Irina; Mija, Alice (Applied sciences, 2021)
A bio-based polymeric matrix was developed by the copolymerization of a vegetable oil-based epoxy, epoxidized linseed oil (ELO), with dodecenyl succinic anhydride (DDSA). To obtain eco-friendly bio-composites, this matrix was combined with a natural filler: spruce bark powder (SB) with its hydrochar (HC) in various proportions ranged from 1 to 30 wt.%. The reactivities of these formulations were studied by DSC analysis that highlighted that both fillers have a high catalytic effect on the ELO–DDSA crosslinking reaction. The complementary studies by TGA, DMA, tensile tests, water absorption and Shore tests had shown that both HC and SB bring improvements to the mechanical properties of the composites, fulfilling multiple roles: (i) Both act as co-reactants in the copolymerization mechanism; (ii) HC acts as reinforcement, consolidating the network and providing stiffness and rigidity; and (iii) SB acts as plasticizer for reducing the brittle character of the epoxy resins.